The inlA Gene of Listeria monocytogenes LO28 Harbors a Nonsense Mutation Resulting in Release of Internalin - Jonquières, Renaud (American Society for Microbiology, 1998)
Internalin is a surface protein that mediates entry of Listeria monocytogenes EGD into epithelial cells expressing the cell adhesion molecule human E-cadherin or its chicken homolog, L-CAM, which act as receptors for internalin. After observing that entry of L. monocytogenes LO28 into S180 fibroblasts, in contrast to that of EGD, did not increase after transfection with L-CAM, we examined both the expression and the structure of internalin in strain LO28. We discovered a nonsense mutation in inlA which results in a truncated protein released in the culture medium. Mutations leading to release of internalin were also detected in clinical and food isolates. These results question the role of internalin as a virulence factor in murine listeriosis.